Reviewing ESP Teacher Education Model: Teachers’ Role - Silvani Umar Ali; Samsudin Hi Adam (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
English for Specific Purpose (ESP) course has been taught over the years in many in Indonesia. In recent years, there has been widespread demand for English language in Indonesia. The development of global market makes people need English in their job environment in order to perform well in their respective fields and to compete in international dimension. Many educational institutions offer a program of ESP courses to meet students’ future career need in global trend. In this case, teachers of English who just teach English for general purpose try to do many efforts to be professional ESP teacher However, the ESP teaching practice in national wide are confronting with several serious problems. One of the major problems lies on its teachers. This paper tries to analyze the present situation of ESP teacher education model in Indonesian context particularly in teachers’ role. Then, it will be analyzed the existing of ESP school in other countries. The last, the writer will offer a model of ESP teacher education that best suit ESP school in Indonesia.